A Fraud Detection Implementation Of Decision Tree C4.5 Algorithm For Fraud Detection On Anonymous Credit Card Transaction - Ulfa Nur Ulfa Mauludina; Dhian Satria Yudha Kartika; Ananda Devi Muri Utomo (International Journal of Data Science, Engineering, and Analytics, 2022)
The development of technology today makes credit cards seen as a solution to problems that are not difficult and practical in conducting transactions at a bank. Not only is it easy to use when making payments, but using a credit card also doesn't require many requirements. However, with the increase in the use of credit cards, there are several emergencies of criminal acts that can cause losses for customers and banks. This study uses a dataset from the Kaggle website, which amounts to 56,962 original data from a bank in Europe. Data Mining has been reviewed as the best solution to solving this problem, so in this study, the Decision Tree C4.5 method will be used in detecting fraud in credit card transactions. Keywords: Credit Card. Fraud, Data Mining